KLASIFIKASI JENIS BIMBINGAN DAN KONSELINGSISWA SMKN 1 KEDIRI MENGGUNAKAN NAIVEBAYES CLASSIFIER DAN NEAREST NEIGHBOR - Daniati, Erna - (Nusantara of Engineering (NOE), 2014)
Abstract – Students counseling grouping at “SMKN 1 Kediri “ is based on the school’sexperience in guiding and providing counselingto students  in the past. The form of counselingassistance provided is learning, subjects aresocial assistance, career guidance, mentoringpersonality, spirituality, and special assistance.Naive Bayes Classifier method can be used togroup the data of a student in a group counselingclass. Nearest Neighbor method can be used as amethod of comparison of the classificationprocess. If of all students both methods are equally good..Key Word – Naïve Bayes Classifier , NearestNeighbor , Counseling.Abstrak – Pengelompokan konselingsiswa di SMKN 1 Kediri didasarkan padapengalaman sekolah dalam membimbing danmemberikan konseling pada siswa di masayang lalu. Bentuk konseling yang diberikanadalah pendampingan Belajar,pendampingan mata pelajaran bersifatsosial, pendampingan karir, pendampingankepribadian, kerohanian, danpendampingan khusus. Metode Naïve BayesClassifier dapat digunakan untukmengelompokkan data seorang siswa dalamkelompok kelas konseling. Metode NearestNeighbor dapat dipakai sebagai metodepembanding dari sisi proses klasifikasinya.Jika dari seluruh siswa Kata kunci – Naïve Bayes Classifier ,Nearest Neighbor , Konseling.